2016
DOI: 10.1177/0959354316650943
|View full text |Cite
|
Sign up to set email alerts
|

Whose mind? Two interpretations of what it is to directly perceive other minds

Abstract: According to direct perception theory (DPT) people understand each other’s minds by way of perceiving each other’s behavioral engagements in the world. I argue that DPT admits of two interpretations. One interpretation is found in Searle’s social ontology. The other interpretation departs from an enactivist account of social cognition. Both can make sense of what it is to perceive other minds, but in two different ways. The first claims that people can directly perceive states of mind shared in a community. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Perceiving others respond the way you would is seeing them think and feel like you in the shared milieu (Rietveld, 2012a, 2012b; Rietveld & Kiverstein, 2014). More radically, perhaps, it has been suggested that DPT allows for perception of collective states of mind (Lo Presti, 2016b, p. 425). Considering that some behavioral responses in a shared social environment (e.g., religious or economic) are responses to objects and events (e.g., holy or monetary objects and events) collectively intended to play significant social or institutional roles (e.g., Searle, 2010, 2015), behavioral responses can reveal collective attitudes.…”
Section: The Oppositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceiving others respond the way you would is seeing them think and feel like you in the shared milieu (Rietveld, 2012a, 2012b; Rietveld & Kiverstein, 2014). More radically, perhaps, it has been suggested that DPT allows for perception of collective states of mind (Lo Presti, 2016b, p. 425). Considering that some behavioral responses in a shared social environment (e.g., religious or economic) are responses to objects and events (e.g., holy or monetary objects and events) collectively intended to play significant social or institutional roles (e.g., Searle, 2010, 2015), behavioral responses can reveal collective attitudes.…”
Section: The Oppositionmentioning
confidence: 99%
“…This Sellars–Gibson connection is picked up, very briefly, by McDowell in a footnote of Mind and World (1994, p. 10). To my knowledge, it has otherwise passed unnoticed (but see Lo Presti, 2016b).…”
mentioning
confidence: 97%